Analysis of Student Skills in Developing Mathematics Learning Videos Using ICT-Based Learning Media - Mujtahid, Zainul; Widya, Widya; Rahadi, Irwan; Sinaga, Nurul Afni (LPPM Universitas Terbuka, 2024)
The development of ICT-based learning media can improve the quality of learning. The availability of ICT-based learning media is still limited, while the Merdeka curriculum demands the application of ICT-based learning media in learning. Therefore, prospective teachers must be equipped to develop ICT-based learning media, one of which is learning videos. The type of research is a case study with 29 research subjects (students/prospective teachers) from the mathematics education study program at Malikusaleh University. Data collection is carried out through assessing learning videos made by students. Then, the assessment data is analyzed using a student skills analysis sheet in creating/designing a learning video. The assessment results show that students have reached the